2018
DOI: 10.1002/lary.27713
|View full text |Cite
|
Sign up to set email alerts
|

Middle‐ear dexamethasone delivery via ultrasound microbubbles attenuates noise‐induced hearing loss

Abstract: Objectives/Hypothesis In this study, we expanded our previous investigation by testing the efficiency of trans–round window membrane dexamethasone (DEX) delivery mediated by ultrasound (US)‐aided microbubbles (MBs) and its preventive effects regarding noise exposure in animal models. Study Design Live animal model. Methods Forty‐two pigmented male guinea pigs were divided into the following three groups: an US‐MBs (USM) group, in which the tympanic bulla was filled with DEX and MBs and exposed to US; a round w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…The ultrasound device (ST2000V, Nepa Gene, Chiba, Japan) equipped with a 6mm-diameter transducer was used for irradiation. The optimal US exposure settings had been predetermined in our previous report (Shih et al, 2019). Briefly, the mode was set as follows: frequency 1 MHz, burst rate 250 Hz, burst duration 2 ms, acoustic intensity 3 W/cm 2 (mechanical index [MI] = 0.254) for three or five consecutive 1-min courses; and a 50% duty cycle.…”
Section: Microbubble Preparation and Ultrasound Exposurementioning
confidence: 99%
See 3 more Smart Citations
“…The ultrasound device (ST2000V, Nepa Gene, Chiba, Japan) equipped with a 6mm-diameter transducer was used for irradiation. The optimal US exposure settings had been predetermined in our previous report (Shih et al, 2019). Briefly, the mode was set as follows: frequency 1 MHz, burst rate 250 Hz, burst duration 2 ms, acoustic intensity 3 W/cm 2 (mechanical index [MI] = 0.254) for three or five consecutive 1-min courses; and a 50% duty cycle.…”
Section: Microbubble Preparation and Ultrasound Exposurementioning
confidence: 99%
“…As described and schematically illustrated in our previous study (Shih et al, 2019), guinea pigs were administered xylazine i.m. (Rompun; Bayer, Leverkusen, Germany) at 10 mg/kg and ketamine (Imalgene; Merial, Lyon, France) at 80 mg/kg.…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study demonstrated the practical application of using USMB to increase the permeability of the RWM, in which a surgical technique was used to remove the temporal bone and expose the membrane (17). We subsequently expanded that technique to explore the delivery of dexamethasone mediated by USMB and its protective effects against noise exposure in animal models (18). In clinical practice, the transcanal approach is often indicated for transtympanic injections of drugs to treat various inner ear diseases and is applied to most patients undergoing endoscopic ear surgery (19).…”
Section: Introductionmentioning
confidence: 99%